Limitation on the ownership of foreign parties of real estate in Iceland - Gunnarsson, Eyvindur G. (Stjórnsýslustofnun, 2012)
According to Article 72, paragraph 2, of the Icelandic Constitution the right of foreign parties to own real property interests or shares in business enterprises in Iceland may be limited by law. Limitation on the ownership of foreign parties of real estate is currently regulated by Law No. 19/1966 on the ownership and use of real estate. The first legislation regarding this matter was Law No. 63/1919 on the same topic. The general rule under current law is that foreign parties, persons and legal entities, may not acquire rights over real estate in Iceland unless they meet stringent requirements regarding residence etc. Parties who enjoy rights under the EEA Agreement, however, enjoy broader rights. The same applies to parties who are authorized to conduct business in Iceland. The article concludes that Law No. 19/1966 should be revised. Samkvæmt 2. mgr. 72. gr. stjórnarskrárinnar er heimilt með lögum að takmarka rétt erlendra aðila til að eiga fasteignaréttindi eða hlut í atvinnufyrirtæki hér á landi. Um takmörkun á eignarhaldi erlendra aðila á fasteignum hér á landi gilda nú lög nr. 19/1966 um eignarrétt og afnotarétt fasteigna en fyrstu lögin sem sett voru um þessi efni voru lög nr. 63/1919 um sama efni. Meginregla gildandi laga er sú að erlendum aðilum, einstaklingum og lögaðilum, er óheimilt að öðlast fasteignaréttindi hér á landi nema að uppfylltum ströngum skilyrðum, svo sem um lögheimili o.fl. Aðilar sem njóta réttar samkvæmt EES-samningnum njóta þó rýmri réttar. Auk þess hafa erlendir aðilar, sem hafa heimild til að stunda atvinnurekstur á Íslandi, ákveðinn rétt. Komist er að þeirri niðurstöðu að rétt sé að taka lög nr. 19/1966 til endurskoðunar.